2005
DOI: 10.1142/s0192415x05003107
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Energy Transfer During Acupuncture?

Abstract: Acupuncture therapy is based on the principle of restoring equilibrium of the body's energy state by regulating the flow of Qi in the corresponding meridians and acupoints. The purpose of this study was to determine whether bio-energy transfer occurs during acupuncture of the meridians. We treated 20 normal healthy subjects with acupuncture and measured changes in the direct current (DC) potential between the stomach meridian points ST-39 and ST-37 in response to invasive insertion of a needle at ST-36. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…They reported that bio-energy was transferred from practitioner to receiver based on the potential change that occurred during bare handed acupuncture stimulation. 27 However, they could not show the energy flow in the body by acupuncture stimulation, and it was limited to stomach meridian. Spaulding et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that bio-energy was transferred from practitioner to receiver based on the potential change that occurred during bare handed acupuncture stimulation. 27 However, they could not show the energy flow in the body by acupuncture stimulation, and it was limited to stomach meridian. Spaulding et al.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Due to the difficulty in defining or measuring Qi, few studies have been conducted on the mechanism of Qi or energy flow by acupuncture treatment, and all related studies have focused on the electrical properties such as the conductivity of acupuncture points 22 , 23 , 24 , 25 or measured biopotential changes only at some acupuncture points, not all meridians. 26 , 27 , 28 Thus, we aimed to observe the changes in electrical energy and to compare the electrical potential between the acupuncture and non-acupuncture points in twelve meridians.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, when the sympathetic nerve is active, acupuncture activates the opposite system of the parasympathetic system, stimulating peristalsis, thus maintaining the homeostasis of the body. These results finally indicate that acupuncture affects the activity of physiological processes, at least to a certain extent via parasympathetic cholinergic fibers (Lee et al, 2005;Takewaki et al, 2005). According to modern knowledge, it is actually accepted that the three gases, commonly known as a toxic gases, carbon monoxide (CO), nitric monoxide (NO), and hydrogen sulfide (H 2 S), are generated endogenously in living organisms by stimulating receptors of the cholinergic system (Mustafa, Gadalla, & Snyder, 2009;Szabo, 2010).…”
Section: Possible Mechanical and Bioelectrical Mechanism Of Transmissmentioning
confidence: 94%
“…It seems that acupuncture therapy is based on the principle of restoring equilibrium of the body's energy state in the corresponding meridians and acupoints. These results suggest that there may be bioenergy (Qi) transfer during acupuncture along the meridians, and this transferred bio-Qi seems to act as an electromotive force, which is purported to remove the stagnation or blockage of energy and restore an equilibrium state (Lee et al, 2005). According to Eastern philosophy and medicine, Qi energy represents an invisible life force underlying all phenomena.…”
mentioning
confidence: 99%
“…In other words, qi interacts with time and flows through the body. Based on this model, acupuncture works by regulating the circulation of qi ( 7 ). Given the relationship among qi, time and meridian, the method of Zi-Wu-Liu-Zhu is useful in calculating the optimum time to administer acupuncture at a particular meridian ( 8 ).…”
Section: Introductionmentioning
confidence: 99%